The Rule Minimum Age of Marriage in Islamic Family Law in the Muslim World - Mega Puspita; Nindya Octariza (International Journal of Social Science and Religion (IJSSR), 2022)
Questioning the issue of the minimum rules for marriage in Islam itself is not explained in detail about the minimum age for marriage. In jurisprudence, scholars of different schools of thought have different opinions regarding the minimum age limit for marriage, which in essence, someone who has reached the age of puberty can already get married. This article aims to discuss the minimum rules for marriage that are applied in every Muslim country in the world. The minimum marriage rules discussed are in Indonesia, Algeria, Bangladesh, Egypt, Iraq, Jordan, Lebanon, Libya, Malaysia, Morocco, Yaman, Pakistan, Somalia, Syria, Tunisia, Turkey, Afghanistan. The minimum age difference in some Muslim countries including Indonesia stems from the way each country determines the direction of their legislation, especially in marriage laws. Because in some countries it refers to the school of jurisprudence that it uses. Then, the purpose of the minimum age in marriage is to minimize the risks that will occur in marriage such as: Divorce caused by the immaturity of the child's mentality, difficulties in fulfilling family livelihoods, the potential for the birth of an unhealthy child caused by the biological immaturity of the child, and potential for maternal death due to pregnancy at an early age.